Cytokines as biomarkers of inflammatory response after open versus endovascular repair of abdominal aortic aneurysms: a systematic review - TSILIMIGRAS Diamantis I; SIGALA Fragiska; KARAOLANIS Georgios; NTANASIS-STATHOPOULOS Ioannis; SPARTALIS Eleftherios; SPARTALIS Michael; PATELIS Nikolaos; PAPALAMPROS Alexandros; LONG Chandler; MORIS Demetrios (Acta Pharmacologica Sinica, 2018)
The repair of an abdominal aortic aneurysm (AAA) is a high-risk surgical procedure related to hormonal and metabolic stress-related response with an ensuing activation of the inﬂammatory cascade. In contrast to open repair (OR), endovascular aortic aneurysm repair (EVAR) seems to decrease the postoperative stress by offering less extensive incisions, dissection, and tissue manipulation. However, these beneficial effects may be offset by the release of cytokines and arachidonic acid metabolites during intra-luminal manipulation of the thrombus using catheters in endovascular repair, resulting in systemic inﬂammatory response (SIR), which is clinically called post-implantation syndrome. In this systematic review we compared OR with EVAR in terms of the post-interventional inﬂammatory response resulting from alterations in the circulating cytokine levels. We sought to summarize all the latest evidence regarding post-implantation syndrome after EVAR. We searched Medline (PubMed), ClinicalTrials.gov and the Cochrane library for clinical studies reporting on the release of cytokines as part of the inﬂammatory response after both open/conventional and endovascular repair of the AAA. We identified 17 studies examining the cytokine levels after OR versus EVAR. OR seemed to be associated with a greater SIR than EVAR, as evidenced by the increased cytokine levels, particularly IL-6 and IL-8, whereas IL-1β, IL-10 and TNF-α showed conﬂicting results or no difference between the two groups. Polyester endografts appear to be positively correlated with the incidence of post-implantation syndrome after EVAR. Future large prospective studies are warranted to delineate the underlying mechanisms of the cytokine interaction in the post-surgical inﬂammatory response setting.